Perilaku Konsumtif Dalam Kajian Psikologi Tasawuf Robert Frager - Muhammad Yudhistir; Al Fath Cahya Ryandana; Muhammad Abdul Halim Sani (Jurnal Budi Pekerti Agama Islam, 2024)
Currently, we live with various conveniences, especially when shopping. These conveniences produce many benefits, but there are also some negative impacts, one of which is consumptive behavior. Consumptive behavior is the action of someone who uses or buys something, either goods or services excessively. Usually prioritizing the urge of desire rather than need. This urge of desire is what in the perspective of Sufism psychology according to Frager is something that needs to be minimized, the reason researchers chose Frager's concept of Sufism psychology is because consumer behavior is closely related to nafs, and Frager is a Sufism psychology figure who is most detailed in describing the concept compared to other figures such as Al Ghazali. This study aims to see how consumer behavior is studied in the theory of Sufism psychology according to Robert Frager and how psychospiritualism is applied in minimizing consumptive behavior. The method used in this study is a descriptive qualitative method with a form of library research. According to Frager's study of Sufism psychology, consumptive behavior can be categorized into tyrannical nafs and lawwamah nafs, but consumptive behavior can be reduced when it is in the category of inspired nafs. Meanwhile, consumptive behavior will completely disappear if it is at the level of peaceful nafs, pleased nafs, approved nafs, and pure nafs. The psychospiritual applications that can be applied include: fasting, seclusion, serving brothers, and remembering death.